Pelatihan Daring Software Geogebra dan Scilab bagi Guru Matematika di Provinsi Banten - Syamsuri Syamsuri; Hepsi Nindiasari; Anwar Mutaqin; Cecep Anwar HF Santosa (Universitas Mathla'ul Anwar Banten, 2021)
GEOGEBRA AND SCILAB SOFTWARE ONLINE TRAINING FOR MATHEMATICS TEACHERS IN BANTEN PROVINCE. The utilization of Geogebra dan Scilab in mathematics learning is certainly inseparable from the role of teachers. This article aims to identify geogebra software's online training for mathematical learning. This online training was conducted synchronously 4 times in the period of September 2020, and accompanied asynchronously through the Edmodo application. Teachers who actively participate in online training are about 68 teachers. The teacher's response to learning by utilizing Geogebra and Scilab software depends on the teacher's initial ability regarding the software. The online training is able to add to the teacher's knowledge about mathematics learning software, especially Geogebra and Scilab.